Heterogeneous consumer preferences for product quality and uncertainty - Wolfgang Maennig; Steffen Q. Mueller (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2021)
We provide evidence for heterogeneous consumer preferences for product quality and game outcome uncertainty (GOU) in Major League Baseball. Using attendance data from 2013 to 2019, we explore functional data clustering techniques to detect common patterns in predictive margins of team-specific winning probability. As a central result, we identify five groups of teams with similar GOU effects. However, only a few teams' fans show GOU preferences that resemble the typical hump-shape that is postulated by the uncertainty of outcome hypothesis; the largest cluster is comprised of teams with fans whose attendance behavior is relatively insensitive to differences in GOU.
Keywords: D12; L15; L2; L83; Z2; 330; Consumer demand; Heterogeneous preferences; Product quality; Uncertainty of outcome hypothesis; Clustering; Functional data analysis